Exosomes Promote Pre-Metastatic Niche Formation in Gastric Cancer - Gao, Jing; Li, Song; Xu, Qian; Zhang, Xue; Huang, Miao; Dai, Xin; Liu, Lian (Frontiers in Oncology, 2021)
Gastric cancer has a high rate of metastasis, during which pre-metastatic niches (PMN) provide a supportive environment for the upcoming tumor cells. Exosomes are bilayer vesicles secreted by cells containing biological information that mediates communication between cells. Using exosomes, gastric cancer cells establish PMN remotely in multifarious perspectives, including immunosuppression, stroma remodeling, angiogenesis, mesothelial mesenchymal transformation, and organotropism. In turn, the cell components in PMN secrete exosomes that interact with each other and provide onco-promoting signals. In this review, we highlight the role of exosomes in PMN formation in gastric cancer and discuss their potential values in gastric cancer metastasis diagnosis, prevention, and treatment.